Strategi Pemasaran Usaha Mandiri Berbasis Pemberdayaan Limbah Daun Ketapang : (Studi di Wisata The Pikas Artventure Banjarnegara) - Nur Soimah (Pusat Riset dan Inovasi Nasional, 2024)
The Pikas Artventure in Banjarnegara, located on the banks of the long and wide Serayu River, offers nature tourism including rafting, outbound, paintball, and river camping. Established in 2009, this tourist attraction is known as a pioneer of rafting on the Serayu River. Utilizing ketapang trees that grow in tourist areas, ketapang leaf waste that is usually not used is now processed into valuable products, such as liquid to balance the pH of the water used in ornamental fish farming. This opens up new business opportunities that have a positive impact on the surrounding community. This study aims to explore the business marketing strategy based on waste empowerment in The Pikas Artventure, using a qualitative approach and descriptive-analytical analysis techniques. By implementing B2B, B2C, and C2C marketing strategies, ketapang leaf liquid products have been successfully marketed locally and online, expanding the market reach around Banjarnegara. The study also identified barriers, such as staff shortages, that affected services, as well as offering solutions such as increasing headcount and developing internal communications.